CARBON EMISSION REDUCTION QUANTIFICATION THROUGH GREEN BUILDING AS A MITIGATION EFFORTS ON CLIMATE CHANGE AND GLOBAL WARMING - Anggoro., dkk, Suryo (BPPT)
Mitigation and adaptation are two approaches for taking policy action to address climate change impacts. Mitigation activities seek to reduce the sources or enhance the sinks of greenhouse gases, most notably carbon dioxide (CO2), and adaptation is to adjust human systems in response to actual or expected climatic stimuli or their effects. One signifance difference between mitigation and adaptation approach is emission reduction expressed in CO2-equivalent units. Emission reductions through mitigation activities can be easily measured. Green building is one of mitigation activities and this paper is to analyze policy impacts through green building approach in CO2 reduction equivalent units.keywords : green building, mitigation, climate change